An Erratic Exanthem: Postvaricella Guillain-Barre Syndrome With Facial Diplegia. Issue 4 (July 2021) - Arora, Aanchal; Meena, Sanjay Kumar; Mahto, Subodh Kumar; Goel, Atul
Abstract : Abstract: Varicella zoster (Chickenpox) usually occurs in childhood due to infection with varicella zoster virus. It manifests as an acute febrile exanthem which is usually self-limiting. Varicella zoster virus infection, in most cases, provides lifelong immunity to an individual after primary infection. In adults, primary varicella is uncommon, and most cases occur as a result of reactivation of the dormant virus. Subsequently, in adults, varicella infection can behave erratically to present with various unusual systemic and neurological complications, which are again uncommonly seen after primary varicella. The most common neurological complications seen are herpes zoster, postherpetic neuralgia, cerebellitis, meningoencephalitis and rarely stroke, myelitis, and Guillain-Barre syndrome. We hereby present the case of a young male who developed Guillain-Barre syndrome with facial diplegia and bulbar palsy after primary varicella infection.